Risk Perception as Mediator in the Effect of Financial Literacy to Entrepreneurial Orientation among MSMEs - Carina, Tiara; Mentari, Ni Made Indah; Permana Putra, I Dewa Made Arik; Sari, Melani Gita; Purnama Dewi, Ni Putu Tasiya (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 17 Nomor 1 Tahun 2023DO - 10.24843/MATRIK:JMBK.2023.v17.i01.p03, 2023)
This study aims to analyze the mediating role of risk perception on the effect of financial literacy to entrepreneurial orientation. From a total population of 32,026 MSMEs in Denpasar, 244 samples were taken through purposive sampling. Data were collected through the administration of Financial Literacy Instruments (rxx=0.639-0.891; r=0.974), Risk Perception Instruments (rxx=0.873-0.956; r=0.989), and Entrepreneurship Orientation Instruments (rxx=0.894-0.988; r=0.988). According to data analysis with Partial Least Square (PLS), it was found that financial literacy significantly affects entrepreneurial orientation; financial literacy significantly influences risk perception; risk perception significantly influences entrepreneurial orientation; and risk perception partially mediates the effect of financial literacy to entrepreneurial orientation in MSMEs in Denpasar. It was found that 49.8% of the variation in the entrepreneurial orientation variable is explained by financial literacy and risk perception variables, while the remaining 50.2% is contribution of other variables outside this research. Keyword : risk perception, financial literacy, entrepreneurship orientation, MSME